(untitled) - Bentley, Jerry H. (New York, 2003)
This groundbreaking world history text offers a fresh approach that takes the global nature of its subject seriously by exploring networks of interaction from the earliest times to the present. By examining the world as a whole and focusing on the links and interactions that have always existed among societies, it presents an alternative to Eurocentric history. For this reason, world history instructors have long been anticipating its arrival.
Keywords: Lịch sử thế giới,World history,Intercultural communication; History